2016
DOI: 10.5115/acb.2016.49.4.223
|View full text |Cite
|
Sign up to set email alerts
|

Galanin's implications for post-stroke improvement

Abstract: Stroke leads to a variety of pathophysiological conditions such as ischemic infarct, cerebral inflammation, neuronal damage, cognitive decline, and depression. Many endeavors have been tried to find the therapeutic solutions to attenuate severe neuropathogenesis after stroke. Several studies have reported that a decrease in the neuropeptide regulator ‘galanin’ is associated with neuronal loss, learning and memory dysfunctions, and depression following a stroke. The present review summarized recent evidences on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Relevant clinical data 10 show that patients with ischemic stroke are very prone to depression after onset, characterized by low spirits, lack of interest and sense of worthlessness, which are mostly accompanied by sleep disorders, cognitive defects and physical symptoms. The meta-analysis found that the incidence of depression two weeks - seven years after stroke was as high as 33%.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant clinical data 10 show that patients with ischemic stroke are very prone to depression after onset, characterized by low spirits, lack of interest and sense of worthlessness, which are mostly accompanied by sleep disorders, cognitive defects and physical symptoms. The meta-analysis found that the incidence of depression two weeks - seven years after stroke was as high as 33%.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Kofler et al [ 13 ] showed that galanin is involved in skin immunity, as its expression was demonstrated to be upregulated in inflammation-remodeled tissue. In poststroke inflammation, galanin regulates the release of inflammatory cytokines and inflammatory cell infiltration in the brain [ 14 ]. Galanin regulates cellular responses by activating three distinct G-protein-coupled receptors, galanin receptor 1 (GalR1), GalR2, and GalR3, which diverge in their distributions, pharmacology, and signaling.…”
Section: Introductionmentioning
confidence: 99%
“…1 According to the location of the lesion, the size of the area of inadequate perfusion, and the amount of collateral blood flow, dysfunctions such as anxiety, depression, motor, sensory, cognitive, and communication disorders are observed in patients following a stroke. 2 A sensorimotor disorder might include somatosensory changes that impair movement control and joint stabilit. 1 During the stroke, the upper motor neuron is reached, with a change in muscle tone with sagging and weak muscles related to the glenohumeral joint.…”
Section: Introductionmentioning
confidence: 99%